Mid-Century Climate Change Impacts on Ouémé River Discharge at Bonou Outlet (Benin) - LAWIN, AGNIDÉ EMMANUEL; HOUNGUE, Rita; N'TCHA M'PO, Yekambessoun; HOUNGUE, Rholan Nina; ATTOGUINON, Andé; AFOUDA, ABEL (My University, 2019)
This work focuses on impacts of climate change on Ouémé River discharge at Bonou outlet based on four global climate models (GCM) over Ouémé catchment from 1971 to 2050. Empirical quantile mapping method is used for bias correction of GCM. Furthermore, twenty-five rain gauges were selected among which are three synoptic stations. The semi-distributed model HEC-HMS (Hydrologic Modeling System from Hydrologic Engineering Center) is used to simulate runoff. As results, HEC-HMS showed ability to simulate runoff while taking into account land use and cover change. In fact, Kling–Gupta Efficiency (KGE) coefficient was 0.94 and 0.91 respectively in calibration and validation. Moreover, Ouémé River discharge is projected to decrease about 6.58 m3 /s under Representative Concentration Pathways (RCP 4.5) while an insignificant increasing trend is found under RCP 8.5. Therefore, water resource management infrastructure, especially dam construction, has to be developed for water shortage prevention. In addition, it is essential to account for uncertainties when designing such sensitive infrastructure for flood management
Keywords: Climate change; HEC-HMS; Ouémé River catchment